2021
DOI: 10.2147/cia.s306894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ICT-Based Multicomponent Program on Body Composition and Cognitive Function in Older Adults: A Randomized Controlled Clinical Study

Abstract: Purpose Information and communication technology (ICT)-based training devices for older adults’ care related to dementia are being developed to enhance older adults’ cognitive functions. Older adults who require bicycle training devices can improve muscle strength and balance of lower limbs by continuously contracting and relaxing lower-limb muscles and improving cognitive function to prevent dementia. This study was conducted to investigate the effects of an ICT-based multicomponent program on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Regarding depression and QoL, there were no statistically significant changes in the experimental group; however, there was a trend toward improvement. Regarding the SGDS-K, as in a previous study, 48 we could not find a significant difference in the time × group interaction. This may be due to ceiling effects; the participants were independent elderly individuals who were capable of conducting the interventions, and their baseline SGDS-K score was low, indicating a high function for depression.…”
Section: Discussionsupporting
confidence: 54%
“…Regarding depression and QoL, there were no statistically significant changes in the experimental group; however, there was a trend toward improvement. Regarding the SGDS-K, as in a previous study, 48 we could not find a significant difference in the time × group interaction. This may be due to ceiling effects; the participants were independent elderly individuals who were capable of conducting the interventions, and their baseline SGDS-K score was low, indicating a high function for depression.…”
Section: Discussionsupporting
confidence: 54%
“…Women, who are apparently better suited to multiple roles than men, may not adequately buffer lost roles after retirement (Gyasi et al, 2019; Rafael et al, 2021; Tan et al, 2019) and focus on those in which they feel more responsibility (such as grandmothers and caregivers), which could cause opposite effects on cognitive health (Burn & Szoeke, 2015; Jutras & Veilleux, 1991) (Table 3, rows 13–15). Participating in more activities and interests is related to a better adaptation to the aging process due to the increase in cognitive reserve that each new activity and role produces (Clare et al, 2017; Gulley et al, 2011; Kielhofner, 2007; Kim et al, 2021; Mao et al, 2020; Oakley et al, 1986; Zhu et al, 2017). Our results are congruent with the multirole theory and MOHO (Ahrens & Ryff, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The studies concluded that chair-based exercise programs have positive effects on physical and cognitive functioning in older adults, thus improving their physical and mental well-being. Upper and lower limb: Two of the studies conducted quasiexperimental studies [67,138], one conducted randomized controlled intervention [137], one conducted a randomized controlled pilot trial [14], and the others didn't mention the study conducted. Two of the studies included only female participants [67,130], and one included only male participants [37].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of participants ranged from 20 to 63. Two of the studies were conducted in England [14,130], one was conducted in South Korea [137], one in Malaysia [138], and one in Brazil [139]. The study [67] concluded that chair yoga improves upper and lower limb strength.…”
Section: Study Characteristicsmentioning
confidence: 99%